Sistem Informasi Pengolahan Data Laporan Kejahatan Atau Tindak Kriminal Pada Polres Labuhanbatu Berbasis Web - Sihombing, Maikel Rinaldi (Journal of Computer Science and Information System(JCoInS), 2022)
Crime is a deviant act or behavior that is detrimental to the community by violating existing laws and regulations. One of the main causes of crime is economic needs and also the use of drugs. Crime can happen anywhere and anytime, even the perpetrators do not hesitate to hurt their victims. To give a deterrent effect to the perpetrators, the police then act decisively by arresting the perpetrators who are disturbing the community. The method used for this research is interview. By asking directly the police officers who work in the Satreskrim section. The purpose of this research is to find out what is asked by the Satreskrim to the perpetrators and how the perpetrator's data will be stored and used for what other things. With this aim, the benefit that can be obtained is that the perpetrator's data in the Satreskrim will be used for other purposes such as making a police record certificate. To keep all data of suspects or perpetrators safe, a system that is connected to the database is needed. This system will later aim to store all data on suspects who have dealt with the police, which then can still be accessed for the purpose of making police records or other interests.